RNAseq reveals weed‐induced PIF3‐like as a candidate target to manipulate weed stress response in soybean. Issue 1 (25th February 2015) - Horvath, David P.; Hansen, Stephanie A.; Moriles‐Miller, Janet P.; Pierik, Ronald; Yan, Changhui; Clay, David E.; Scheffler, Brian; Clay, Sharon A.
Summary: Weeds reduce yield in soybeans ( Glycine max ) through incompletely defined mechanisms. The effects of weeds on the soybean transcriptome were evaluated in field conditions during four separate growing seasons. RNASeq data were collected from six biological samples of soybeans growing with or without weeds. Weed species and the methods to maintain weed‐free controls varied between years to mitigate treatment effects, and to allow detection of general soybean weed responses. Soybean plants were not visibly nutrient‐ or water‐stressed. We identified 55 consistently downregulated genes in weedy plots. Many of the downregulated genes were heat shock genes. Fourteen genes were consistently upregulated. Several transcription factors including a PHYTOCHROME INTERACTING FACTOR 3 ‐like gene ( PIF3 ) were included among the upregulated genes. Gene set enrichment analysis indicated roles for increased oxidative stress and jasmonic acid signaling responses during weed stress. The relationship of this weed‐induced PIF3 gene to genes involved in shade avoidance responses in Arabidopsis provide evidence that this gene may be important in the response of soybean to weeds. These results suggest that the weed‐induced PIF3 gene will be a target for manipulating weed tolerance in soybean.